Indexing Profile of English-Language Journals of the University of Tehran Based on Indexing Criteria of International Citation Databases - Niloofar Solhjoo (Central Library of Astan Quds Razavi, 2016)
Objective: This study aims to determine the feasibility and possibility of indexing English-language journals published by the University of Tehran in international citation indexes (e.g. Web of Science and Scopus). It would also help to find out the reasons why the majority of these journals are not yet indexed in international citation indexes. This study also provides some strategies to increase the international visibility and accessibility of these journals. Materials and Methods: This descriptive survey examined English-language journals published by Scientific Journals Database of Tehran University, available at https://journals.ut.ac.ir. We have used a combination of qualitative and quantitative measures such as journal citation analysis and a checklist. Citation analysis data was collected from Scopus and Google Scholar, and the checklist was designed upon indexing criteria of Web of Science Core Collection Journal Selection Process and Scopus Content Advisory Board. Results: Findings indicate that the total number of citations per journal was low and therefore only 15 percent of these journals were indexed in international databases and there were only two journals comply with all of the minimum acceptance criteria. Some reasons why they are not yet indexed by international citation databases are the irregularity in publishing, lack of description of the peer-review process and lack of publication ethics and malpractice statement. However, the strong points of these journals are proper publication archive, accessibility, and readability of the content to international readerships. Conclusion: This study helps publishers, editors and decision-makers to improve the quality of international journals and give them the rank and the position of being welcomed by a wider scholar community and accepted by international citation databases.